How Does Fingolimod (Gilenya®) Fit in the Treatment Algorithm for Highly Active Relapsing-Remitting Multiple Sclerosis? - Fazekas, Franz; Bajenaru, Ovidiu; Berger, Thomas; Hojs Fabjan, Tanja; Horvat Ledinek, Alenka; Jakab, Gábor; Komoly, Samuel; Kobys, Tetiana; Kraus, Jörg; Kurča, Egon; Kyriakides, Theodore; Lisý, Lubomír; et al. (Frontiers in Neurology, 2013)
Multiple sclerosis (MS) is a neurological disorder characterised by inflammatory demyelination and neurodegeneration in the central nervous system (CNS). Until recently, disease modifying treatment was based on agents requiring parenteral delivery, thus limiting long-term compliance. Basic treatments such as beta-interferon provide only moderate efficacy, and although therapies for second-line treatment and highly active MS are more effective, they are associated with potentially severe side effects. Fingolimod (Gilenya®) is the first oral treatment of MS and has recently been approved as single disease-modifying therapy in highly active relapsing-remitting multiple sclerosis (RRMS) for adult patients with high disease activity despite basic treatment (beta-interferon) and for treatment-naïve patients with rapidly evolving severe RRMS. At a scientific meeting that took place in Vienna on November 18th, 2011, experts from 10 Central and Eastern European countries discussed the clinical benefits and potential risks of fingolimod for MS, suggested how the new therapy fits within the current treatment algorithm and provided expert opinion for the selection and management of patients.